2022
DOI: 10.1126/sciadv.abq0593
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Exposure Assessment Tool (CEAT): Exposure quantification based on ventilation, infection prevalence, group characteristics, and behavior

Abstract: The coronavirus disease 2019 (COVID-19) Exposure Assessment Tool (CEAT) allows users to compare respiratory relative risk to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for various scenarios, providing understanding of how combinations of protective measures affect risk. CEAT incorporates mechanistic, stochastic, and epidemiological factors including the (i) emission rate of virus, (ii) viral aerosol degradation and removal, (iii) duration of activity/exposure, (iv) inhalation rates, (v) venti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Generally, masks require a proper fit to prevent inhaling the potentially harmful nonfiltered air. However, air leakage arises when the mask is deformed, which is generated from a cough, sneezing, talking, or even just breathing. , Thus, it is imperative for mask fabrics to possess commendable mechanical properties and deformation resilience. During the course of wearing a mask, it is primarily subjected to vertical compression resulting from the airflow and the bending and stretching force caused by facial movements .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, masks require a proper fit to prevent inhaling the potentially harmful nonfiltered air. However, air leakage arises when the mask is deformed, which is generated from a cough, sneezing, talking, or even just breathing. , Thus, it is imperative for mask fabrics to possess commendable mechanical properties and deformation resilience. During the course of wearing a mask, it is primarily subjected to vertical compression resulting from the airflow and the bending and stretching force caused by facial movements .…”
Section: Resultsmentioning
confidence: 99%
“…However, making informed decisions in public health crises can be extremely challenging without accurate data and evidence, particularly in situations like pandemics, where disjointed and disparate information from multiple sources can result in poor decision-making [ 7 , 47 ]. This challenge was particularly pronounced in terms of ineffective information sharing across different levels of governments, with municipal governments having to take decisions at the local level, without concrete evidence [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these challenges to timely evidence-based decision-making, citizen-driven big data, which is not only timely but also relevant to specific jurisdictions, can transform local jurisdictional decision-making [ 3 , 7 , 49 ]. The digital health dashboard for decision-making that we conceptualized and developed, at its core, addresses these challenges by providing municipal decision makers access to ethically obtained big data from their own citizens to enable evidence-based decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of PVDF-HFP nanofibers or HOF@ PVDF-HFP nanofibers to the DPBF solution in the absence of light did not result in a change in the DPBF absorption spectrum, and the PVDF-HFP nanofibers failed to generate 1 O 2 under green LED irradiation and therefore cause the absorption peak of DPBF to decrease. But the absorption peak at 410 nm decreased rapidly in HOF@PVDF-HFP nanofibers under green LED illumination because of the decomposition of DPBF caused by 1 O 2 (Figures S10 and S11, Supporting Information). It was found that the levels of 1 O 2 generated by the same mass of composite nanofibers in 20 min are in the order: 10 wt.% > 0.5 wt.% > 5 wt.% > 1 wt.% HOF-101-H@PVDF-HFP (Figure S12, Supporting Information).…”
Section: O 2 Generation Properties Of Hof @Pvdf-hfp Nanofibersmentioning
confidence: 99%
“…The Corona Virus Disease 2019 (COVID‐19) outbreak has had a huge impact not only on public health but also on the economy and society. [ 1 ] Unfortunately, COVID‐19 is only one of the many pathogenic diseases that threaten public health. Antibiotics are a solution to the treatment of bacterial or fungal infections, but their misuse can lead to the evolution of highly threatening drug‐resistant bacteria, [ 2 ] and it is important to find or develop new antimicrobial strategies with materials other than antibiotics.…”
Section: Introductionmentioning
confidence: 99%